2001
DOI: 10.1073/pnas.121016998
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclooxygenase-2 by Epstein–Barr virus latent membrane protein 1 is involved in vascular endothelial growth factor production in nasopharyngeal carcinoma cells

Abstract: Cyclooxygenase-2 (COX-2) is an inducible form of COX and is overexpressed in diverse tumors, raising the possibility of a role for COX-2 in carcinogenesis. In addition, COX-2 contributes to angiogenesis. The Epstein–Barr virus (EBV) oncoprotein, latent membrane protein 1 (LMP1), is detected in at least 70% of nasopharyngeal carcinoma (NPC) and all EBV-infected preinvasive nasopharyngeal lesions. We found that in specimens of LMP1-positive NPC, COX-2 is frequently expressed, whereas LMP1-negative NPC ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
201
1
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(217 citation statements)
references
References 35 publications
9
201
1
5
Order By: Relevance
“…We also have reported that vascular endothelial growth factor (VEGF) could be an important regulator of angiogenesis in NPC tissue [28,29,30]. In addition to these studies, we reported LMP1 induces VEGF through HIF1α using epithelial cell lines [31].…”
Section: Discussionmentioning
confidence: 79%
“…We also have reported that vascular endothelial growth factor (VEGF) could be an important regulator of angiogenesis in NPC tissue [28,29,30]. In addition to these studies, we reported LMP1 induces VEGF through HIF1α using epithelial cell lines [31].…”
Section: Discussionmentioning
confidence: 79%
“…Celecoxib treatment could remove the negative feedback and lead to COX-2 induction. In addition, Murono et al determined that LMP1 could induce COX-2 expression in NPC cell lines, increase prostaglandin E2 production through COX-2 induction and that celecoxib could inhibit prostaglandin E2 production [39] . Therefore, LMP1 may induce COX-2 expression to up-regulate prostaglandin E2 expression after the inhibition of prostaglandin E2 expression by celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, COX-2 demonstrates a positive regulatory role in lymphangiogenesis [39] . Interestingly, all these factors are induced by the EBV-associated oncoprotein, LMP1, in NPC [8,29,30] . Thus, we expected that LMP1…”
Section: Discussionmentioning
confidence: 99%